REKONSTRUKSI KONSEP CHARACTER BUILDING DI ERA CYBER (INTERNALISASI NILAI-NILA KARAKTER ANAK MELALUI KELUARGA DAN SEKOLAH) - Mutaqin Al Zam-zami (Islamic University of Indonesia, 2018)
At present various facilities and sophistication are offered as an impact of the development of science and knowledge. The impact can be in the form of positive impacts and also negative impacts. Negative impacts that are not minimized by the formation of children’s character will damage human life. That’s why character education should be conceptualized in education both at school and in the family. This scientific article will try to explain how theoretical reconstruction and practice in character building concepts and how to analyze character building concepts so that they can be implemented by families and schools. By conducting library research on various documents, the author can gather that the theoretical construction and practice in the concept of character building starts from the role of the family. In addition, in its implementation, teachers or parents can use various strategies while instilling values related to attitudes and morals. Keywords : value internalization, character building, cyber era